Perancangan Sistem Informasi Pendukung Keputusan Pemilihan Jurusan Kuliah Menggunakan Metode SMART (Current Research in Education: Conference Series Journal, 2023)
Choosing a major in college is one of the important things for every student who will enter higher education. The process of choosing the right major that suits the interests, talents, and potential of the individual can help direct their career and future. To help students in choosing the right major, a decision support system is needed that can process data and provide recommendations for majors that are suitable for the student's profile. To address this problem, a College Major Decision Support System using the SMART method was built. This system can input assessment criteria, alternatives, weights, and produce calculations using the SMART method, namely ranking college majors. This research used the waterfall method, which is a model for developing information systems that go through several stages including requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The results of this study are a decision support system for choosing college majors that can be used to determine the best major to be chosen by users/prospective students or parents in making choices, thus increasing confidence when choosing a major and improving the quality of learning for students who enter the majors of their choice.